(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
The article analyzes the concept of gender identification in literary studies and its relationship to stereotypes. The issues of the formation of female and male characters in literature and their conformity to social and cultural stereotypes are examined. The article analyzes gender stereotypes in classical and contemporary literary works, the character of protagonists, and gender dimensions in their interrelationships. Scientific reflections on the impact of gender stereotypes on social consciousness and culture are also presented.